White coat effect in patients with hypertension - G. F. Andreeva; V. M. Gorbunov; D. N. Antipushina; E. V. Platonova (Столичная издательская компания, 2023)
The article is devoted to various aspects of white coat effect (WCE) in patients with hypertension (HTN). WCE is due to the patient's anxious response to office blood pressure (BP) measurement and is characterized by a BP increase. In patients with HTN, WCE is detected with a high frequency. Pronounced WCE in hypertensive patients is associated with worsening the HTN course and the prognosis of all-cause and cardiovascular mortality. In addition, BP increase in these patients during a doctor's visit may lead to additional prescription of antihypertensive drugs, increasing costs and side effects. To identify WCE, a large number of methods are used, which can be divided into following groups: I - data from clinical and daytime ambulatory blood pressure measurement, II - clinical and home BP assessment, III - only ambulatory BP measurement, IV - clinical and laboratory BP data, and V - only clinical BP measurement. There are following WCE in patients with HTN: female sex, age, never smoking, as well as anxiety, introversion, etc. WCE is due to the patient's anxiety state during office BP measurement and a conditioned reflex BP increase associated both with the physician presence and medical background. Severe WCE in some groups of patients with HTN may be associated with a worse prognosis compared with other hypertensive patients as follows: in individuals with a significant difference between clinical and ambulatory blood pressure levels or between the first and third BP office data, with a combination of resistant HTN and WCE, with WCE increasing from visit to visit, etc.